Emergency remote assessment practices in higher education in sub-Saharan Africa during COVID-19 - Baidoo-Anu, David; Asamoah, Daniel; Quainoo, Eric Atta; Gyamerah, Kenneth; Amoateng, Ernest Y.; Sasu, Ernest Ofori (Frontiers in Education, 2023)
Following the disruptions to in-person schooling during COVID-19 and the need for emergency remote teaching, this study explored the assessment experiences of teacher educators in Ghana. Through a qualitative transcendental phenomenological approach, purposive criterion sampling was used to select 25 teacher educators from 15 teacher training institutions in Ghana who participated in online teaching during COVID-19 school closure. The findings show that teacher-centered approaches to assessment dominate emergency remote assessment practices of teacher educators. Hodgepodge grading and general feedback were more prevalent during remote assessment. Teachers were also found to randomly select a few students to provide individualized feedback due to the large class size. Challenges including limited knowledge of the use of the online teaching platform for assessment, inadequate professional training and access to technological resources, and concerns about academic dishonesty were reported. However, teachers reported that their involvement in abrupt remote teaching and assessment has been a learning opportunity for them to develop new skills, which is imperative for their professional development.